Deterioration in the water quality of an urbanised estuary with recommendations for improvement - JB, Adams; Pretorius, L; Snow, GC (Water SA, 2019)
Water quality characteristics of the heavily urbanised and industrialised Swartkops River and Estuary in the Eastern Cape have been the focus of several studies since the 1970s. Overloaded and poorly maintained wastewater treatment works (WWTWs), polluted stormwater runoff and solid waste have all contributed to the deterioration in the water quality of the river and estuary. The objective of this study was to determine the current water quality status of the Swartkops Estuary, by investigating spatial and temporal variability in physico-chemical parameters and phytoplankton biomass and where possiblerelate this to historical water quality data. The present study found evidence suggesting that water is not flushed as efficiently from the upper reaches of the estuary as was previously recorded. Reduced vertical mixing results in strong stratification and persistent eutrophic conditions with phytoplankton blooms (> 20 μg chl a·L−1), extending from the middle reaches to the tidal head of the estuary. The Motherwell Canal was and still is a major source of nitrogen (particularly ammonium) to the estuary, but the Swartkops River is the primary source of phosphorus with excessive inputs from the cumulative effectof three WWTWs upstream. An analysis of historical water quality data in the Swartkops Estuary (1995 to 2013) shows that all recorded dissolved inorganic phosphorus measurements were classified as hypertrophic (> 0.1 mg P·L−1), whereas 41% of dissolved inorganic nitrogen measurements were either mesotrophic or eutrophic. If nutrient removal methods at the three WWTWs were improved and urban runoff into the Motherwell Canal better managed, it is likely that persistent phytoplankton blooms and health risks associated with eutrophication could be reduced.